Transformations and transfer of Tantra in Asia and beyond - Keul, István (Religion and society 1437-5370, 2012)
pt. 1. South Asia -- pt. 2. Mongolia, Tibet, and China -- pt. 3. Japan -- pt. 4. ... and beyond